Interruption to antiplatelet therapy early after acute ischaemic stroke: a nested case-control study - Mazlan-Kepli, Wardati; Macisaac, Rachael L.; Walters, Matthew; Bath, Philip Michael William; Dawson, Jesse (Wiley, 2017)
Aims: Antiplatelet drugs are often discontinued early after ischaemic stroke, either because of poor compliance, complications or withdrawal of care. It is unclear whether this places patients at increased risk of recurrence. We explored the association between cardiovascular event rate and persistence with prescribed antiplatelet drugs. Methods: We used a matched case–control design using the Virtual International Stroke Trials Archive (VISTA). Cases were patients who had an acute coronary syndrome, recurrent stroke or transient ischaemic attack within 90 days post-stroke and were matched for age ± 10 years and sex with up to four controls. Antiplatelet use was categorized as persistent (used for >3 days and continued up to day 90), early cessation (used antiplatelet <3 days) or stopped/interrupted users (used for >3 days but stopped prior to day 90). These categories were compared in cases and controls using a conditional logistic regression model that adjusted for potential confounders. Results: A total of 970 patients were included, of whom 194 were cases and 776 were matched controls. At 90 days, 10 cases (5.2%) and 58 controls (7.5%) stopped/interrupted their antiplatelet. The risk of cardiovascular event was not different in stopped/interrupted users (adjusted odds ratio 0.70, 95% confidence interval 0.33, 1.48; P = 0.352) and early cessations (adjusted odds ratio 1.04, 95% confidence interval 0.62, 1.74; P = 0.876) when compared to persistent users. Conclusion: We found no increased risk in patients who stopped and interrupted antiplatelets early after stroke but the study was limited by a small sample size and further research is needed.